Perylenes Bearing Multiple H-Bonding Donor and Acceptor Groups for Photonic Applications - Mostafanejad, Seyedeh Melika (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Construction of supra-molecular self-assembled building blocks due to their relevance in organic, inorganic, polymeric compounds as well as biological systems has attracted many attentions and various well-defined supra complexes with different sizes and shapes in the range of 1-100 nm dimensions have been prepared. Modification of perylene dye at imides or bay positions leads to high solubility of the product along with wide range of absorption expands to near infrared region. In the present study, Three different perylene diimide which two of them were symmetrical (N,N'-bis-[2-(5-carboxamidyl-3-cyano-4-methyl)-thienyl]-3,4,9,10-perylene bis (dicarboximide) TPDI and N,N'-bis-[3-((2-methyl-5-pyrimidinyl) methyl)-5-(2-hydroxyethyl)-4-methylthiazolium] perylene-3,4:9,10-tetracarboxylic diimide TCPDI and one was highly soluble asymmetrical (N-(dehydroabietyl)-N'-[3-((2-methyl-5-pyrimidinyl) methyl)-5-(2-hydroxyethyl)-4-methylthiazolium] perylene-3,4,9,10-tetracarboxylic diimide TAPDI with donor-acceptor-donor (DAD systems) building block have been synthesized, in order to change the photophysical and photochemical properties of the diimides, 1,7-symmetrically substituted perylenebis (dicarboximide) dyes (N,N'-di((s)-1-phenylethyl)-1,7-di(3,5-diamino-pyrimidoxyl) perylene-3,4,9,10-tetracarboxy diimide BPY-PPDI, N,N'-bis-[3-((2-methyl-5-pyrimidinyl) methyl)-5-(2-hydroxyethyl)-4-methylthiazolium]-1,7-di-(2-[3[(4-amino-2-methylpyrimidin-5-yl) methyl]-4-methyl-1,3-thiazol-3-ium-5yl] ethoxy-perylene-3,4:9,10-tetracarboxylic diimide BTC-TCPDI and N,N'-bis-(dehydroabietyl)-1,7-di-(2-[3[(4-amino-2-methylpyrimidin-5-yl) methyl]-4-methyl-1,3-thiazol-3-ium-5-yl] ethoxyperylene-3,4:9,10-tetracarboxylic diimide TC-APDI with electron donating groups have been synthesized in good amount of product under mild conditions, The products have been purified and optical, thermal and electrochemical properties of them were measured and characterized carefully. Keywords: Perylene, thiophene, vitamin, bay-substitution, hydrogen bonding.

ÖZ: Günümüzde organik, inorganik, polimerik bileşiklerin ve biyolojik sistemlerdeki önemi nedeniyle kendiliğinden düzenlenme özelliğine sahip supramoleküler madde sentezi çok dikkat çekmekte ve 1100 nm aralığında farklı boyut ve şekillerde çeşitli iyi tanımlanmış supra kompleks maddeler hazırlanmaktadır. Perilen boyalarının imid ve körfez pozisyonlarındaki yer değiştermesi ürünün çözünürlüğünün arttırmasıyla birlikte absorbsiyonun kızılötesi bölgesine kadar genişlemesine öncülük etmektedir. Bu çalışmada, ikisi simetrik (N,N’bis[2(5karboksiamidil3siyano4metil) tiyenil]3,4,9,10-perilenbis(dikarboksimid) TPDI ve N,N'bis[3((2metil5pirimidinil) metil) 5(2hidroksietil) 4metilthiazoliumklorür] perilen3,4:9,10-tetrakarboksilik diimid TCPDI ve biri büyük ölçüde çözünür olan asimetrik (NdehidroabiyetilN'[3((2metil5pirimidinil) metil) 5-(2hidroksietil) 4metilthiazoliumklorür] perilen3,4,9,10tetrakarboksilik diimid TAPDI üç farklı perilendiimid donörakseptördonör (DAD sistemi) yapı taşı ile sentezlenmiştir. Bu diimidlerin fotofiziksel ve fotokimyasal özelliklerini değiştirmek için, 1 ve 7 pozisyonundan simetrik olarak yer değiştirilen perilen bis(dikarboksiimid) boyaları (N,N'di((S)1feniletil)1,7di(3,5diaminopirimidoksilperilen3,4:9,10tetrakarbosilik diimid BPYPPDI, N,N'bis-[3((2metil5pirimidinil)metil)5(2-hidroksietil) 4metilthiazoliumklorür]1,7-di(2[3[(4amino2metilpirimidin5il) metil]4metil1,3tiyazol3yum5il] etoksi perilen3,4:9,10tetrakarboksilik diimid BTCTCPD ve N,N'bis(dehidroabiyetil)1,7ditiyazolyum klorür perilen3,4:9,10tetrakarboksilik diimid TCAPDI elektron verici gruplarla birlikte ılımlı koşullarda iyi miktarda ürün sentezlenmiştir. Sentezlenen ürünler saflandırılmış ve optik, termal ve elektrokimyasal özellikleri ölçülmüş ve dikkatlice tanımlanmıştır. Anahtar kelimeler: Perilen, tiyofen, vitamin, bay-substitution, hidrojen bağı.
Doctor of Philosophy in Chemistry. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2018. Co-Supervisor: Prof. Dr. Saim Özkar, Supervisor: Prof. Dr. Huriye İcil
Keywords: Chemistry Department; Dyes--Chemistry; Perylene Dyes; Perylene; thiophene; vitamin; bay-substitution; hydrogen bonding